Biodiesel Production from Rubber Seed Oil via Esterification Process - Widayat Widayat; S Suherman (International Journal of Renewable Energy Development, 2012)
One promise source of alternative energy is biodiesel from rubber seed oil, because the raw materials available in plentiful quantities and can be renewed. In addition, the rubber seed is still lack of utilization, and Indonesia is one of the largest rubbers producing country in the world. The objective of this research is to studied on biodiesel production by esterification process. Parameters used in this study are the ratio of catalyst and temperature and its influence on the characteristics of the resulting biodiesel product. Characterization of rubber seed include acid content number analysis, saponification numbers, density, viscosity, iodine number, type of free fatty acids and triglyceride oils. The results of analysis showed that rubber seed oil content obtained is 50.5%. The results of the GCMS analysis showed that a free fatty acid level in rubber seed is very high. Conversion into bio-diesel oil is obtained by at most 59.91% and lowest 48.24%.